2011
DOI: 10.1007/s11269-011-9801-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Scour Downstream of a Ski-Jump Bucket Using Support Vector and M5 Model Tree

Abstract: Estimation of scour downstream of a ski-jump bucket has been a topic of research among hydraulic engineers. For estimation of scour downstream of ski jump bucket, several empirical models are in use. In recent years, there has been emphasis to develop models which are capable of producing scour with high accuracy. Use of Artificial Neural Network (ANN) approach to model depth, width and length of scour hole indicates that performance of ANN models is far better than existing empirical models. At present, use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…nique implemented for predicting the scouring depth at downstream of ski-jump bucket. Goyal and Ojha [27] developed the ANN, SVM, and M5 Model Tree for predicting the scour depth at downstream of ski-jump bucket. They considered various scenarios with regard to the a ective parameters during the development of mentioned soft computing techniques.…”
Section: Results Of Mars Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…nique implemented for predicting the scouring depth at downstream of ski-jump bucket. Goyal and Ojha [27] developed the ANN, SVM, and M5 Model Tree for predicting the scour depth at downstream of ski-jump bucket. They considered various scenarios with regard to the a ective parameters during the development of mentioned soft computing techniques.…”
Section: Results Of Mars Modelmentioning
confidence: 99%
“…In the eld of mathematical modeling, using both of CFD and soft computing techniques was reported by Xiao et al [11].Nowadays, by advancing the soft computing techniques in the most areas related to hydraulic engineering, investigators have tried to use these techniques for predicting the scouring phenomena [12][13][14][15][16][17][18][19], speci cally scour depth at downstream of ip bucket. In this regard, using the Arti cial Neural Networks (ANNs), Genetic Programming (GP), Support Vector machine and M5 Model Tree, Group Method of Data Handling (GMDH), and Adaptive Neuro Fuzzy Inference System (ANFIS) can be mentioned [20][21][22][23][24][25][26][27][28][29][30][31][32]. Based on the reports, the precision of all the soft computing techniques was much more than the empirical formulas.…”
Section: Introductionmentioning
confidence: 99%
“…which is most commonly used to nonlinearly map the samples into a high-dimensional space to handle nonlinear problems (Goyal and Ojha, 2011). Moreover, the optimum values of the regularization cost parameter (C), which controls the model's tolerance to error and the size of error insensitive zone (e), need to be determined.…”
Section: Support Vector Regression (Svr)mentioning
confidence: 99%
“…In the last decade, several studies reported the use of support vector regression (SVR) in civil and water resources engineering related applications (Dibike et al, 2001;Cigizoglu, 2005;Pal and Goel, 2006;Firat and Gungor, 2009;Goel and Pal, 2009;Goyal and Ojha, 2011). The results obtained from these studies showed that the SVR provided better results compared with the neural network approach.…”
Section: Introductionmentioning
confidence: 99%
“…In order to model scouring, a variety of soft computing schemes have been used in recent years, such as an artificial neural network (ANN) to predict scour below a ski-jump bucket spillway (Azmathullah, Deo, & Deolalikar, 2005) and culvert outlets (Azamathulla & Haque, 2012), classification and regression trees to estimate wave-induced scour around a circular pile (Ayoubloo, Etemad-Shahidi, & Mahjoobi, 2010), an M5 model tree to estimate scour downstream of a ski-jump bucket spillway (Goyal & Ojha, 2011), an adaptive network based on fuzzy systems to determine scour around an arch-shaped bed sill (Keshavarzi, Gazni, & Homayoon, 2012), linear genetic programming to predict scour around a circular pile (Guven, Azamathulla, & Zakaria, 2009), and the group method of data handling to predict scour downstream of a ski-jump bucket spillway (Najafzadeh, Barani, & Hessami Kermani, 2014).…”
Section: Introductionmentioning
confidence: 99%